2018
DOI: 10.1111/1758-2229.12682
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular aminopeptidase modulates biofilm development of Pseudomonas aeruginosa by affecting matrix exopolysaccharide and bacterial cell death

Abstract: Biofilm bacteria are embedded within a self-secreted extracellular matrix that contains a considerable amount of proteins including many extracellular enzymes. However, little is known about the roles of such enzymes in biofilm development. Here, we studied Pseudomonas aeruginosa aminopeptidase (PaAP, encoded by PA2939 that we named the gene as paaP in this study), a quorum-sensing-regulated enzyme and one of the most abundant extracellular proteins in the biofilm matrix of this opportunistic pathogen and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…aeruginosa forms biofilm communities called pellicles at the air-liquid interface. During pellicle formation, the bacteria attach to the culture container, and biofilm development can be quantitatively assessed using a crystal violet stain (27) or live-dead staining of the pellicle bacteria (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa forms biofilm communities called pellicles at the air-liquid interface. During pellicle formation, the bacteria attach to the culture container, and biofilm development can be quantitatively assessed using a crystal violet stain (27) or live-dead staining of the pellicle bacteria (28).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhao et al showed that PaAP can affect PAO1 P. aeruginosa biofilm pellicles formed in cultures using Jensen’s medium at 30°C (28). While the body of this work mainly focused on a late-stage phenotype, they also observed that PaAP deletion led to increased biomass in early biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…on the involvement of PslG in biofilm disruption, which was also, intriguingly, PaAP-dependent 531 33 . However, in this case, biofilm disruption was found to take place in late log-stage biofilms 532 under nutrient-limiting conditions such that the lack of PaAP lead to cell lysis, releasing the 533 periplasmic PslG enzyme.…”
Section: Discussion 504mentioning
confidence: 98%
“…Several factors from P. aeruginosa are known to facilitate biofilm detachment directly, including 483 those that can break apart the biofilm structure by enzymatic or biochemical means. We studied 484 the impact of three known disruption factors on this phenotype: rhamnolipids 35,36 , and the 485 exopolysaccharide hydrolases PslG 33,36 and AlgL 36 . Vesicles were isolated from cultures of 486 PA14 transposon mutants with a deletion in each potential target and evaluated for their ability 487 21 to reduce the biomass of 4.5 hpi S470∆PaAP coculture biofilms.…”
Section: Protease Inhibitors Decrease Biofilm Detachment Activity Of mentioning
confidence: 99%
“…However, bacterial factors have been identified that can contribute to human disease in a counterintuitive fashion. Longitudinal studies that follow the progression of P. aeruginosa strains from early colonization through chronic infection have shown that the bacteria quickly evolve and adapt to the conditions found in the CF lung, and that many of the genetic changes seen in chronic P. aeruginosa strains function to decrease overall bacterial pathogenicity [32][33][34] . For example, mucA mutations, which downregulate the expression of virulence-associated type III secretion systems, are frequently observed 35,36 .…”
Section: Discussionmentioning
confidence: 99%